2020
DOI: 10.1371/journal.ppat.1009147
|View full text |Cite
|
Sign up to set email alerts
|

Mutations altering acetylated residues in the CTD of HIV-1 integrase cause defects in proviral transcription at early times after integration of viral DNA

Abstract: The central function of the retroviral integrase protein (IN) is to catalyze the integration of viral DNA into the host genome to form the provirus. The IN protein has also been reported to play a role in a number of other processes throughout the retroviral life cycle such as reverse transcription, nuclear import and particle morphogenesis. Studies have shown that HIV-1 IN is subject to multiple post-translational modifications (PTMs) including acetylation, phosphorylation and SUMOylation. However, the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 71 publications
2
31
0
Order By: Relevance
“…Noteworthy, the competition of Tat ARM with IN for TAR binding has also been reported elsewhere 8 . Our data are also fully consistent with recent evidences of the implication of IN in the transcription of the provirus at early times after integration and in a Tat-independent manner 32 . The authors found that mutation of four lysine residues within the IN-CTD dramatically reduced proviral transcription since all of them are involved in the binding of IN to the viral RNA 8,26 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Noteworthy, the competition of Tat ARM with IN for TAR binding has also been reported elsewhere 8 . Our data are also fully consistent with recent evidences of the implication of IN in the transcription of the provirus at early times after integration and in a Tat-independent manner 32 . The authors found that mutation of four lysine residues within the IN-CTD dramatically reduced proviral transcription since all of them are involved in the binding of IN to the viral RNA 8,26 .…”
Section: Discussionsupporting
confidence: 92%
“…b Structural model of TAR RNA obtained with RNA Fold WebServer 63 64 predicting a minimum free energy of −29.60 kcal/mol. c Representative native 6% polyacrylamide gel illustrating the Electrophoretic mobility shift assay (EMSA) showing the interaction of IN-FLm with TAR RNA or an unstructured RNA 50-mer (AG (50) -mer) labelled with 32 P (black star). The RNA substrates (50 nM) were incubated with various concentrations of IN-FLm or without protein (TAR RNA: 0; 100, 200, 400 nM of IN-FLm; AG (50) -mer RNA: 0 or 400 nM of IN-FLm).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations